Visible Light Photocatalysis of BiOI and Its Photocatalytic Activity Enhancement by in Situ Ionic Liquid Modification - Wang, Yunan; Deng, Kejian; Zhang, Lizhi (Journal of physical chemistry. C, 2011)
In this study, we investigate the photocatalysis mechanism of BiOI in detail and therefore demonstrate that the photocatalytic activity of BiOI could be enhanced greatly by in situ modification of an ionic liquid [Bmim]I (1-buty-3-methylimidazolium iodide). The ionic liquid modified BiOI (IL-BiOI) was prepared by reacting bismuth nitrate with [Bmim]I in water at 70 °C, where the ionic liquid could act as both iodine source and surface modified agent. On degradation of methyl orange (MO) under visible light irradiation (λ > 420 nm), IL-BiOI photocatalyst exhibited superior photocatalytic activity to the unmodified counterpart synthesized in the absence of [Bmim]I. The effects of ionic liquid modification on the photocatalytic activity enhancement were systematically investigated. We found that IL modification could trap the photoexcited electron at conduction band of BiOI to inhibit the recombination of photoinduced electron–hole pairs and thus enhance its photocatalytic activity on the degradation of organic pollutants.